Implementation of Problem Based Learning to Increase Scientific Explanation Skill in Biology Learning about the Environment - Monika Lintang Laksmi (Commonwealth of Learning, 2021)
This research aimed to describe and find out whether implementation of Problem-Based Learning can improve scientific explanation skills in biology learning about the environment. The research method was Classroom Action Research through the implementation of Problem-Based Learning. This classroom action research consisted of two cycles, which were concluded by planning, acting, observing and reflecting. The research subject was anatural science class consisting of 34students. Data were collected by essay test, observation method, interviews and documentation. Data were validated by the triangulation technique consisting of three components: data reduction, data presentation and conclusion. The research results showedimprovement in the scientific explanation skills of students on the implementation of Problem Based Learning. The percentage improvement of students' scientific explanation was 61% in claim, 53% in evidence, and 51% in reasoning.